Analisis Kinerja Operasional Pelayanan Kapal Dan Barang Di Pelabuhan Malundung Tarakan - Belo, Alprisca Toding (Jurnal Sistem Transportasi & Logistik, 2025)
The purpose of this study was to determine the Operational Performance of Ship and Goods Services at the Malundung Tarakan Port in 2022. The data collection technique was carried out by the author by collecting field data (field research) and collecting library (library research). In this study the author uses a quantitative method, which emphasizes the analysis of data collected from field survey results. The data obtained from the survey results were then analyzed and compared with the standards specified in the Peraturan Dirjen Perhubungan Laut No. HK 103/2/18/DJPL-2016 Tentang Standar Kinerja Operasional Pelayanan Pelabuhan, the results of the discussion were that the Ship Service Performance while in the Malundung Tarakan Harbor had good performance as a result of Waiting Time (WT) 1 Hour, Approach Time (AT) 1.47 Hours, Berthing Time (BT) 43.6 Hours, Effective Time (ET) 28.3 Hours and Not Operation Time (NOT) 12.34 Hours, while for the ratio of ships while in berths (ET/BT) obtained sufficient results well that is 65.8 Hours. The performance of loading/unloading flows at the Malundung Tarakan Port in 2022 received a good score with an average value of 24 T/G/H and 21 B/C/H. Performance Utilization of Facilities related to the Berth Occupancy Ratio (BOR) obtained unfavorable results, namely 79.86%, while the Yard Occupancy Ratio (YOR) obtained good results with an average value of 36.3%.